2019
DOI: 10.1186/s13018-019-1301-z
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor-1 and VEGF are prognostic factors for osteosarcoma

Abstract: Background Osteosarcoma is aggressive and prognostic biomarkers are important to predict the outcomes of surgery and chemotherapy. Here, we investigated the potential of transferrin receptor-1 (TfR1) and vascular endothelial growth factor (VEGF) as prognostic markers of osteosarcoma. Methods TfR1 and VEGF in osteosarcoma samples from a cohort of 53 osteosarcoma patients were detected by immunohistochemistry analysis. The correlation of TfR1 and VEGF levels with clinicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Therefore, in order to further explore the value of IRGs in OS prognosis, we constructed a prognostic signature consisting of 13 prognostic-associated DEIRGs, which has a high diagnostic prognostic efficacy. The high expression lever of GNRH1 49 , BRAF 50 , PSMD10 51 and VEGFA 52 closely correlated with the growth, metastasis, and angiogenesis of OS. The high expression of GAL 53 , 54 , TNFRSF11B 55 and STC2 56 are linked to prostate cancer and colorectal cancer development and a worse prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, in order to further explore the value of IRGs in OS prognosis, we constructed a prognostic signature consisting of 13 prognostic-associated DEIRGs, which has a high diagnostic prognostic efficacy. The high expression lever of GNRH1 49 , BRAF 50 , PSMD10 51 and VEGFA 52 closely correlated with the growth, metastasis, and angiogenesis of OS. The high expression of GAL 53 , 54 , TNFRSF11B 55 and STC2 56 are linked to prostate cancer and colorectal cancer development and a worse prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have reported that TFR1 is involved in kinds of diseases, including cancers, anaemia, and neurodegenerative diseases. Most importantly, TFR1 was verified to be abnormally expressed in various cancers, and some experimental and clinical drugs and antibodies targeting this protein have shown strong anti-tumour effects [38][39][40][41][42][43][44][45][46]; herein, TFR1 is suggested to be a potential molecular biomarker for targeted cancer diagnosis and therapy. SAHH, encoded by the AHCY gene, belongs to the adenosylhomocysteinase family and is a competitive inhibitor of S-adenosyl-L-methionine-dependent methyltransferase reactions and might play a key role in the control of methylation by regulating the intracellular concentration of adenosylhomocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor tyrosine kinases Her2 and VEGF have been thought to have potential as targets in the treatment of refractory or metastatic osteosarcoma. High Her2 expression has been correlated with poor histological response and poor outcome [93] and high expression of VEGF has been associated with worse disease-free and overall survival [374,375]. A clinical trial combining a Her2-inhibitor with conventional chemotherapy did not improve outcomes for metastatic patients [229], however, suggesting that targeting Her2 does not have a clinical effect on resistant disease, which is consistent with other findings correlating high Her2 levels with good clinical outcomes and those finding no correlation at all between Her2 and outcome in osteosarcoma [96][97][98].…”
Section: Signal Transductionmentioning
confidence: 99%
“…It has recently been found that expression of transferrin receptor-1 (TfR1) significantly correlates with poor survival, and that high expression of this factor was associated with a high histological grade, high Enneking staging, and metastases [375]. TfR1 is the main protein responsible for iron uptake, and abnormal iron metabolism is associated with tumorigenesis [402], suggesting that abnormal iron metabolism may be associated with chemotherapy resistance.…”
Section: Other Factors Linked To Drug Resistance In Osteosarcomamentioning
confidence: 99%